Psychosocial Factors and Juvenile Homicide in Argentina - Wiese, Renata (International journal of offender therapy and comparative criminology, 2019)
Although knowledge on and prevention of juvenile homicide are crucial for social welfare and have been approached through different methodological instruments, this behavior is still quite difficult to be addressed. In this study, we have analyzed several psychological and social factors that could be theoretically related to juvenile homicidal behavior. Our case-control study included young (M = 16.8 years) males institutionalized in the Province of Buenos Aires, Argentina, under judicial order for crime. Out of 195 cases, 130 had committed homicide, 15 had repeated homicide, and 50 had attempted homicide. The control group comprised 305 young males who had committed other types of crimes. Self-reported and informant-reported instruments and professional assessment were used: Consideration of Future Consequences (CFC) Scale, Weinberger Adjustment Inventory (WAI), Resistance to Peer Influence (RPI), Psychopathy Checklist-Youth Version (PCL-YV), and Inventory of Callous Unemotional Traits (ICU). Differences between indicators of the psychological and social dimensions were not statistically significant. Only Factor 4 of the PCL-YV showed statistically significant difference. However, the relevance of this result is under discussion.